SAT0615 The RS11803505 IL-23R polymorphism is a risk factor for the development of msus-detected erosions in patients with systemic lupus erythematosus. (15th June 2017) - Perricone, C; Ceccarelli, F; Iorgoveanu, V; Ciccacci, C; Rufini, S; Alessandri, C; Spinelli, FR; Cipriano, E; Novelli, G; Valesini, G; Borgiani, P; Conti, F
Abstract : Background: Articular involvement is a frequent and invalidating manifestation in patients with Systemic Lupus Erythematosus (SLE) ranging from arthralgia to erosive arthritis. Bone erosions are far less common in SLE but require a different management and may display a distinct pathogenesis. Musculoskeletal ultrasonography (MSUS) has proven useful in the assessment of inflammatory arthritis and it is now known that MSUS is more sensitive than radiography in detecting bone erosions. Objectives: We aimed at analyzing, in a large monocentric cohort of SLE patients who suffered from arthritis, the relationship between 31 polymorphisms in 18 genes previously associated with SLE or other autoimmune/inflammatory arthritis [1] and the presence of bone erosions detected by MSUS. Methods: Consecutive SLE patients who complained articular involvement (defined by 1997 ACR criteria, i.e. ≥2 joints with tenderness, swelling or effusion) were enrolled. Patients RF+ve and/or anti-CCP+ve were excluded. Thirty-one SNPs in 18 genes (STAT4, IL10, IL23R, IRAK1, PSORS1C1, HCP5, MIR146a, PTPN2, ERAP1, ATG16L1, IRGM, TRAF3IP2, VKORC1, CCR5, ATG5, TRAF6, TNFSF4, CD40) were genotyped by allelic discrimination assays. Bilateral high-resolution MSUS of the hands and feet was performed. Erosion number was recorded, the presence of erosive damage was assessed with a dichotomous score. Results: Clinical and laboratory features of the 95 enrolled patients are described in table. The presence of MSUS-detected erosions was demonstrated in 15/95 (15.8%) patients, with a mean±SD of 0.44±1.34. Bone erosions were more frequently observed at II metacarpophalangeal joint of the hands (29.4%), followed by the V metatarsophalangeal joint of the feet (16.1%). An association was found between anti-dsDNA and the presence of bone erosions (P=0.009, Fisher's exact test); indeed, all the 15 patients (100%) with bone erosions were anti-dsDNA positive vs 54/80 (67.5%) of those without erosions. After Bonferroni correction, IL-23R rs11803505 was found to be associated with the presence of MSUS-detected bone erosions both at genotypic (Pc =0.045) and at the allelic level [Pc =0.022, OR=8.27 (95% CI 1.02–66.90)]. The association of bone erosions with anti-dsDNA and IL-23R11803505 genotype was confirmed in a logistic regression analysis including also age, sex and disease duration (P=0.005 and P=0.02, respectively). Conclusions: Our study is the first reporting a contribution of IL-23R gene to MSUS-detected erosive damage in SLE. IL-23R gene is a key player in several inflammatory conditions such as psoriatic arthritis, and variants of this gene have already been associated with peripheral erosive disease [2]. Moreover, we confirmed an association between anti-dsDNA and bone erosions in SLE [3], suggesting that the presence of these antibodies is linked with a more aggressive inflammatory pattern of disease. References: Ciccacci C, Perricone C, et al. PLoS One. 2014. Jadon D, Tillett W, et al. Rheumatology (Oxford). 2013. Galvão V, Atta AM, et al. Joint Bone Spine. 2009. Disclosure of Interest: None declared